(3QSGdI aj UaGJ GdYdIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3abhdi JhcdJ Ydi ehdGfG Ld PcQg CQOJ Hg dGghJ ehdGfG s
(3BNQgG (B:s
(3hjYJbOhf ajg GdedMOhf hjJbhdhf GdeTQchf YdhkG cHjQkG Je GdLRA GdChd hjJdhg GdKGfi hehdGfG MSHfG hfYe GdeYjf GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds